Reduced thermal tolerance in a coral carrying CRISPR-induced mutations in the gene for a heat-shock transcription factor - Cleves, Phillip A.; Tinoco, Amanda I.; Bradford, Jacob; Perrin, Dimitri; Bay, Line K.; Pringle, John R. (Proceedings of the National Academy of Sciences - PNAS, 2020)
Reef-building corals are keystone species that are threatened by anthropogenic stresses including climate change. To investigate corals’ responses to stress and other aspects of their biology, numerous genomic and transcriptomic studies have been performed, generating many hypotheses about the roles of particular genes and molecular pathways. However, it has not generally been possible to test these hypotheses rigorously because of the lack of genetic tools for corals or closely related cnidarians. CRISPR technology seems likely to alleviate this problem. Indeed, we show here that microinjection of single-guide RNA/Cas9 ribonucleoprotein complexes into fertilized eggs of the coral Acropora millepora can produce a sufficiently high frequency of mutations to detect a clear phenotype in the injected generation. Based in part on experiments in a sea-anemone model system, we targeted the gene encoding Heat Shock Transcription Factor 1 (HSF1) and obtained larvae in which >90% of the gene copies were mutant. The mutant larvae survived well at 27 °C but died rapidly at 34 °C, a temperature that did not produce detectable mortality over the duration of the experiment in wild-type (WT) larvae or larvae injected with Cas9 alone. We conclude that HSF1 function (presumably its induction of genes in response to heat stress) plays an important protective role in corals. More broadly, we conclude that CRISPR mutagenesis in corals should allow wide-ranging and rigorous tests of gene function in both larval and adult corals.